Ismail Raji al-Faruqi’s thought on Islamization of knowledge and its significance for Islamic education - Muslih, Muslih (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2023)
This paper explores al-Faruqi’s thoughts on the Islamization of knowledge and evaluates the significance of his ideas in the Islamic educational context. The study employs a comprehensive review of al-Faruqi’s writings and contributions to the discourse on the related concept. To establish a comprehensive understanding, the discussion begins with the history of how the ideas on the Islamization of knowledge emerged. Subsequently, it explains al-Faruqi’s concept of Islamization of knowledge, suggesting that all disciplines comprising the humanities, the social, and the natural sciences must be Islamic-based and consistent with Islamic objectives. Furthermore, this paper delves into solving the education problem and the principles of the Islamization of knowledge by discussing the work plans employed. His most remarkable work plan is creating a university textbook tailored to the discipline, incorporating new insight on the meaning of Islam and innovative approaches to realizing that meaning. Fundamentally, the research highlights how al-Faruqi has greatly influenced the development of Islamic education by integrating Islamic principles into knowledge